2021
DOI: 10.3390/su13158127
|View full text |Cite
|
Sign up to set email alerts
|

Green Supply Chain Management: Conceptual Framework and Models for Analysis

Abstract: Sustainability and environmental concerns have been important topics of discussion in recent decades. Green supply chain management assures the effectiveness of public and company policies in greening their operations, increasing the market share, improving the company image and reputation, and increasing profits. The objective of this article is to propose a conceptual framework that considers dimensions, categories, and practices in green supply chain management. After an extensive review of the literature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 77 publications
0
54
0
1
Order By: Relevance
“…For the past two decades, SSCM has focused on integrating environmental, social and economic objectives into all the supply chain processes of large companies [45,46]. Herrmann et al [47], reported that, in recent years, around 70% of the leading companies in any given sector emphasized sustainable development in their work programs. Reports from leading companies confirm that the success of sustainability efforts also depends on collaboration between supply chain actors [48,49].…”
Section: Logistics Supply Chain and Sustainable Supply Chainmentioning
confidence: 99%
See 2 more Smart Citations
“…For the past two decades, SSCM has focused on integrating environmental, social and economic objectives into all the supply chain processes of large companies [45,46]. Herrmann et al [47], reported that, in recent years, around 70% of the leading companies in any given sector emphasized sustainable development in their work programs. Reports from leading companies confirm that the success of sustainability efforts also depends on collaboration between supply chain actors [48,49].…”
Section: Logistics Supply Chain and Sustainable Supply Chainmentioning
confidence: 99%
“…Green supply chain management ensures the effectiveness of public and corporate policies to make their operations cleaner, increasing market share and profits and improving their images and reputations [47].…”
Section: Logistics Supply Chain and Sustainable Supply Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Construction companies have come up with solutions in order to address sustainability. They support national and local development and maintain a sustainable environment (Herrmann et al 2021). Modise (2018) stated that South African construction companies have accentuated the development of a sustainable structure for their activities and accepted global environment and economic changes by promoting growth and up-skilling the workforce with the intention of forming flexible, efficient and effective artisans.…”
Section: Construction Industry In South Africamentioning
confidence: 99%
“…Supply chain sustainability is the management of environmental, social and economic impacts of products and services throughout their lifecycle, and the promotion of good governance practices [1]. Managing supply chain sustainability effectively is required for the promotion of good governance practices [2] and for the proper management of the environmental, social, and economic impacts of products and services throughout their life cycle [3].…”
Section: Introductionmentioning
confidence: 99%